DOXORUBICIN INDUCED NEPHROTOXICITY VIA FREE RADICAL ANTIOXIDANT ACTIVATION IN WISTAR RATS - Ali Asgher Shuja; Sumbul Shamim; Rubina Gulzar; Sumreen Begum; Uzma Shakeel; Nazia Ahmed; Nadia Naeem; Muhammad Arshad (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Anthracycline antibiotics are very effective chemotherapeutic agents. Doxorubicin has broad spectrum of activity against solid tumors and hematologic malignant tumors. The development of nephrotoxicity and cardiomyopathy has greatly limited the use as a highly potent and efficacious anti-neoplastic agent. Adriamycin induced injury appears to be a multifactorial, but free radical generation is one of the most important denominators to most of the proposed mechanisms. The present study aimed to determine the toxic effects of doxorubicin on wistar albino rats. Toxicity study of doxorubicin was observed on LD50 dose 20 mg/kg, respectively. Single Intra-peritoneal injection of doxorubicin was given to male wistar rats which were divided into 3 groups. Group I served as control, Group II treated with doxorubicin 20mg/kg, Group III treated with α-Tocopherol 380 IU/day. The body weights, morphological behavior changes, static movement and oxidant enzymes tests were checked. Single Intra-peritoneal injection of doxorubicin induced significant (p ≤ 0.01-0.001) pathological changes in the health, including general weakness, morphological changes associated with bleeding, change in anti-oxidant enzyme levels and inflammation of the intestine. It was found that after the intraperitoneal administration of doxorubicin the levels of glutathione peroxidase was significantly reduced along the protein oxidation. It is concluded that after the administration of α-Tocopherol the serious effects produced by doxorubicin were minimized and protective effects was seen in rats.